Photoelectrochemical studies on poly[1 - Kasem, Kasem K; Menges, Sara; Jones, Stephenie (Canadian journal of chemistry, 2009)
The compound 2-APPy [1-(2-aminophenyl)pyrrole] as an organic phase in an inorganic-organic semiconductor interface (101) assembly was the subject of photoelectrochemical studies in aqueous solutions. Results show that thin films of poly(2-APPy) can be prepared using oxidative electropolymerization. Furthermore, absorption spectroscopic studies indicate that the protonated 2-APPy polymer's ionization potential (IP) is 4.7 eV, the electron affinity (EA) is 1.90 eV, and a gap of 2.80 eV separates the higher occupied molecular orbital's (HOMO) and lower unoccupied molecular orbital's (LUMO) energy levels of this polymer. Impedance measurements under illumination show an increase in the film charge capacitance compared with those measured under darkened conditions. The behavior of the poly(2-APPy) film as a host for redox-active dopants was also explored. The results show that the film did not alter the redox potentials of a large dopant such as P[Mo.sub.12][O.sub.40.sup.3-]. The photoactivities of the 101 assemblies consisting of 2-APPy and nanoparticles of ZnO, and of [Fe.sub.2][O.sub.3] were investigated using fluorescence emissions. Results show that the fluorescence emissions generated by 2-APPy were quenched by 5% and 55% on ZnO and on [Fe.sub.2][O.sub.3], respectively. The charge injection rate constants, [k.sub.et], at the inorganic metal oxide-2-APPy interface, were calculated.